Cutaneous Verrucous Carcinoma Superimposed on Chronically Inflamed Ileostomy Site Skin: A Case Report - Ali Yaghobi; Payam Azadeh; Behzad Nemati Honar (Iranian Society of Pathology, 2018)
Verrucous carcinoma (VC) is a rare variant of well differentiated squamous cell carcinoma (SCC) which is usually found in oral cavity mucosa. Cutaneous verrucous carcinoma is a rare entity and in this paper we report a 43 years old man with VC superimposed on chronically inflamed skin of ileostomy site. Previously, he was operated to treat rectal adenocarcinoma and has had ileostomy for six months. The skin lesion was resected totally during surgical operation for ileostomy closure. Histopathologic examination confirmed the diagnosis of cutaneous verrucous carcinoma. Post-operative follow up shows no evidence of recurrence after six months. We suggest patient's training for follow up visits in order to early detection of osteomy site complications including neoplastic changes.